State-effects as state power: Expectation, anxiety and fear in the Inambari valley - Lewis Denegri, Francisco (2012)
This ethnography examines the (re)production of the Peruvian state’s power in the fabric of the everyday in the Inambari valley, located in Puno. I argue that focusing on both real and imaginary ‘State-effects’ provides us with a way of tracing the Peruvian state’s power in this context. Further, I examine the social effects of the convergence of two infrastructural projects, both geared towards global, neo-liberal integration, arguing that this convergence led to the creation of a social milieu fraught with feelings of expectation, anxiety, optimism and fear.